2012
DOI: 10.4018/jdldc.2012100102
|View full text |Cite
|
Sign up to set email alerts
|

A Smart University for a Smart City

Abstract: The use of technological devices has changed the way individuals interact with their university environment. This paper examines the use of a smart context as a link between individuals and their university environment through an exemplification of the urgent problems deriving from different domains and technological systems, as well as of information and communication devices employed in university teaching-learning contexts, to improve the quality of higher education and individuals’ cultural life. When does… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 12 publications
0
4
0
1
Order By: Relevance
“…The DSU was self-developed. The measurement of the DSU consists of seven items and it is based on prior literature [1], [2], [7], [18], [22].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The DSU was self-developed. The measurement of the DSU consists of seven items and it is based on prior literature [1], [2], [7], [18], [22].…”
Section: Methodsmentioning
confidence: 99%
“…SU development requires effective KA. Experts, databases, research papers, and other sources are identified, captured, and organized [22]. Smart institutions may acquire information about new trends, innovations, and best practices in higher education.…”
Section: Knowledge Acquisition and Sumentioning
confidence: 99%
“…The first definition of Smart University arose from the concept of Smart City, because any university can be both part of the infrastructure of the city, and the university itself can create its own small city ('college town' or 'university campus'). According to urbanists, Smart University is a concept of integrating technological innovations and the Internet aimed at improving the level of quality, comfort and efficiency of servicing the activities of educational organization (Nuzzaci, & Vecchia, 2012). According to the authors, it is a frame of reference that indicates the presence of technological innovation and the Internet at the university, where students, teachers, staff, and even applicants feel comfortable when they are on its territory.…”
Section: Introductionmentioning
confidence: 99%
“…The Internet allows information to flow freely from one network to another, increasing cultural communication because information passes from one culture to another (i.e. They use it for activities such as shopping, information and socialization, and in many other ways it is considered to be one of the key factors of innovation towards a «Smart Community» (Nuzzaci & La Vecchia, 2012). Cultures can directly communicate with other cultures through elements, signs, systems of signification and cultural symbolism (Nuzzaci, 2011;.…”
Section: Introductionmentioning
confidence: 99%